Efektivitas M-Learning Berbasis Cooperative TGT dalam Meningkatkan Hasil Belajar Bahasa Indonesia Peserta Didik - Mukhamad Nur Khasib; Anas Ahmadi; Inayati Inayati (Lembaga Sosial Rumah Indonesia, 2023)
The aim of this research is to assess student learning outcomes in the Indonesian language subjects Personal Letters and Official Letters using m-learning based on the TGT (Teams Games Tournaments) cooperative learning model at SMP Negeri 1 Mantup Lamongan. This research is classroom action research (PTK) with qualitative and quantitative analysis. This research was carried out in two cycles. This research data was collected from May to June 2023. The subjects of this research were 30 students in class VII-A, 10 men and 20 women. According to the researcher's data analysis, the average student learning outcome before PTK was 50.22. After PTK the average student learning outcome in cycle I was 60.96, while the average student learning outcome in cycle II was 78.96. Based on research findings, the use of m-learning is effective in improving the learning outcomes of class VII-A students at SMP Negeri 1 Mantup Lamongan in Indonesian language subjects for the 2022/2023 academic year.